So High you can’t get over it: Neo-classicism, Modernism and Colonial Practice in the forming of a Twenieth Century Architectural Landmark - Findlay, Michael (Architectural History Aotearoa, 2006)
Amyas Connell (1901-80) was a New Zealand architect and a leading figure in British modernism. His first commission, High and Over (1929-31) for the archaeologist and classical scholar Bernard Ashmole was described as the first fully worked out modernist house built in England. The project drew attention from a wide range of architectural critics including Howard Robertson and the Country Life writer Christopher Hussey. A short film entitled The House of a Dream made by British Pathé ensured the house was seen by the large cinema audience in 1931. High and Over became more contentious over time when Connell’s intention to combine classical and modern design tendencies was criticised by more doctrinaire modernists. High and Over occupies a place where the traditions of classicism and the emergent features of modernism intersect. Connell’s path, if taken, may have produced a distinctively British form of classical modernism. [NEW PARAGRAPH] This paper seeks to establish the context for High and Over from a New Zealand perspective and through comparison with other projects by colonial architects in Britain. Connell’s critical profile has been shaped by the notion that British modernism was in the hands of "Wild Colonial Boys," a soubriquet used to frame Connell’s work in the 1930s by the British writer Dennis Sharp. In this interpretation, the depth of Connell’s experience prior to High and Over is overlooked. Connell’s partnership with the Australian-born Stewart Lloyd Thomson (1902-90) has not been covered in any previous study of the Connell, Ward and Lucas practice. The High and Over project included a number of related structures set in a landscape plan not usually included in analysis of the complex whole. The relationship between the garden plan and the designs of the Armenian architect Gabriel Guévrékian seen at the Paris Exposition and the Villa Noailles at Hyéres (1927) has also not been traversed.